Advantages and disadvantages of two modifications of the biological method of analysis of wheat seed mycobiota - Rozhkova , T. (Quarantine and plant protection, 2022)
Goal. To determine the most effective modification of the biological method of analysis of mycobiota of winter wheat seeds. Methods. Laboratory analysis of mycobiota of winter wheat seeds by biological method on PGA and on filter paper (wet chamber, rolls), determination of fungi on PGA medium on the basis of modern revision of taxa; analytical and mathematical — analysis of the obtained results and their statistical comparison. Results. During the first phytoexpertise of seeds in 2007, a significant percentage of fungal infections was 37.6%, which raised doubts and led to the next area of research — the comparison of modifications of the biological method. In 2008, phytoexpertise of wheat seeds of four varieties (Driada, Podolyanka, Odeska 267, and Pysanka) was carried out on PGA and on paper rolls. Statistical comparison of the results of fungi of all seeds, determined by the two modifications, was insignificant. In 2010, the analysis of seeds on three varieties (Ukrayinka poltavs'ka, Odes'ka 267, and Dons'ka) showed a significant difference between the results obtained on different substrates. More colonies were isolated on the PGA than on paper rolls. Alternaria and Fusarium fungi were isolated more on agar medium than on paper rolls when comparing the characteristics of infection by individual genera. In 2020, we compared the effectiveness of the analysis of seed mycobiota on agar and paper on the variety of Bohdana from the Forest-Steppe and Polissya, finding more isolation of fungal colonies and a wider range of fungi on the PGA. Conclusions. Phytoexpertise of wheat seeds in 2010 showed a significant difference between the amount of total infected seeds and separately seeds with Fusarium and Alternaria fungi on PGA and paper rolls. The analysis of the mycocomplex of seeds at the PDA identified a new direction of research: from the detection of seed contamination to the settlement of fungi, and then — to the analysis of mycobota with the determination of the percentage of genera / species among the total amount of fungi. Analysis of the micocomplex in 2020 on agar and in a wet chamber showed best results of the first modification of the biological method. But it has disadvantages: the growth of polluting fungi, parasitizing mycophilous fungi. Analysis of mycobiota on filter paper has a rapid demonstration result, but does not show the full range of fungi. Therefore, it is better to use agar media for research.